Mineral trioxide aggregate in pulp chamber floor perforation with ten-year follow-up: case report - Wiess Laurencio, Fabrizzio Alfredo (2026)
Endodontic retreatment represents a clinical challenge that requires advanced techniques for filling removal and the repair of structural defects. This report describes the management of teeth 46 and 47, diagnosed as previously treated teeth with chronic apical abscess. The intervention consisted of the removal of cast posts and the treatment of perforations in the pulp chamber floor through the initial application of calcium hydroxide followed by temporary sealing. Endodontic retreatment procedures were performed, and the perforations were sealed using mineral trioxide aggregate. The cores were rebuilt with reinforced composite resin and ceromer crowns were placed. Radiographic follow-up over a ten-year period revealed a progressive reduction in periapical and furcation osteolytic lesions. In conclusion, the use of mineral trioxide aggregate under a rigorous endodontic retreatment protocol provides therapeutic success, supported by clinical stability and long-term resolution of the pathology.